Updates to the China Design Standard for Energy Efficiency in public buildings. (December 2015) - Hong, Tianzhen; Li, Cheng; Yan, Da
Abstract: The China Design Standard for Energy Efficiency in public buildings (GB 50189) debuted in 2005 when China completed the 10th Five-Year Plan. GB 50189-2005 played a crucial role in regulating the energy efficiency in Chinese commercial buildings. The standard was recently updated in 2014 to increase energy savings targets by 30% compared with the 2005 standard. This paper reviews the major changes to the standard, including expansion of energy efficiency coverage and more stringent efficiency requirements. The paper also discusses the interrelationship of the design standard with China's other building energy standards. Furthermore, comparisons are made with ASHRAE Standard 90.1-2013 to provide contrasting differences in efficiency requirements. Finally recommendations are provided to guide the future standard revision, focusing on three areas: (1) increasing efficiency requirements of building envelope and HVAC systems, (2) adding a whole-building performance compliance pathway and implementing a ruleset based automatic code baseline model generation in an effort to reduce the discrepancies of baseline models created by different tools and users, and (3) adding inspection and commissioning requirements to ensure building equipment and systems are installed correctly and operate as designed. Highlights: Updated China Design Standard for Energy Efficiency in Public Buildings GB 50189. Reviewed major changes to the standard: new and increased efficiency requirements. Discussed the standard's interrelations with China's other building standards. The standard GB 50189-2014 was compared with ASHRAE Standard 90.1-2013. Provided recommendations in three areas for future standard revision.